The effect of intermittent training(strength-running) and mini-games training (3 vs3‚ 2vs2) on Kinetic speed With football players. - SADOUKI , Billal (sports creativity, 2025)
This study aimed to find out the effect of intermittent training (strength -running) and mini games training (3 vs 3 .2 vs 2) to improve the Kinetic speed of footballers and to know the best way of training from the other in to develop this physical quality that is mostly considered as decisive to determine The result of the match. In this study, we relied on the experimental approach to experimental design of equal samples thus, we choose intentional sample (n=24) divided into two experimental groups of students group- 07- of the third year -sporting training - speciality : football of the Institute of physical education and sports - university of Algeria 03 school year 2019/2020. It was practised training program on the first experimental group the intermittent training (strength -running) and training program of mini-games on the second group (3 vs 3 . 2 vs 2) then using pre-field tests and post-ones represented in Akramov test with ball and without ball then choosing rolling the ball 30m and speed test of 30m. The study concluded that there is an effect of the two programs to improve the results of tests and that the program of mini-games training is better than the training program of intermittent training.